Multi-principal alloy deposition coating with low expansion coefficient and preparation method thereof
By using electromagnetically assisted laser deposition technology in laser surface engineering technology, Fe-Co-Ni-Cr multi-main alloy powder is used to form a coating with low thermal expansion coefficient and high hardness, which solves the problems of the coating prone to cracking and thermal stress, and achieves the improvement of the mechanical properties of the coating and the improvement of the use efficiency.
Patent Information
- Application Number
- CN202411163679.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-08-23
AI Technical Summary
The coatings formed by existing laser surface engineering technology are prone to cracking, resulting in a decrease in service life, and the thermal stress caused by the difference in thermal expansion coefficients between the coating materials and the matrix materials is difficult to effectively reduce.
Based on Fe powder, Ni powder and Co powder with spontaneous magnet volume effect, combined with the design concept of multi-main high-entropy alloy material, Fe-Co-Ni-Cr multi-main alloy powder is prepared after mixing with Cr powder, and the deposition coating is formed on the surface of the metal matrix through electromagnetically assisted laser deposition. This technology generates Lorentz forces through static magnetic fields and DC currents, improves mass and heat transfer in the melt pool, refines the microstructure of the coating, and reduces the coefficient of thermal expansion.
The formed deposition coating has a low thermal expansion coefficient (average thermal expansion coefficient is 1.8×10-6/K), high hardness (750-860HV), and no defects such as cracks and pores. It has excellent mechanical properties and is suitable for mass production.
Smart Images

Figure CN118880320B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal alloys and relates to a multi-principal-element alloy deposition coating with a low expansion coefficient and a preparation method thereof. Background Art
[0002] Laser surface engineering technology is a new material surface technology that has developed rapidly in the past decade. It is one of the latest fields of material science, involving multiple disciplines such as physics, materials science, chemistry, interface mechanics and metallurgy. Laser surface engineering technology represented by laser metal deposition can achieve accurate control of heat input, obtain coatings with dense structure and superior performance, and solve many technical problems that are difficult to solve with traditional surface strengthening technology. It has become a research hotspot for scholars at home and abroad and has developed rapidly in recent years.
[0003] The coatings formed by surface engineering technologies such as laser metal deposition are prone to cracking, which will cause the service life of the coating to decrease rapidly and greatly reduce the utilization efficiency of the coating. Therefore, the problem of easy cracking of coatings formed by laser metal deposition has always been a common problem that hinders the large-scale application of this technology.
[0004] Residual stress is the main cause of coating cracking, and a large part of the residual stress comes from the thermal stress formed by the difference in thermal expansion coefficients between the coating material and the substrate material. Therefore, reducing the thermal stress caused by the difference in thermal expansion coefficients between the coating material and the substrate material is an effective way to effectively solve the problem of coating cracking. Domestic and foreign scholars have conducted a lot of experimental and theoretical research to solve this problem, including substrate preheating, adjusting processing parameters, introducing transition layers, improving deposition materials, multi-physics field coupling processing, etc. These technologies reduce the crack sensitivity of the coating to a certain extent. However, these technologies also have problems such as low efficiency, complex operation and high cost, and it is difficult to adapt to the requirements of the engineering field for this technology. Summary of the invention
[0005] The purpose of the present invention is to provide a multi-principal alloy deposition coating with a low expansion coefficient and a preparation method thereof, so as to solve the problems of high crack sensitivity and poor mechanical properties of the coating in the existing laser surface engineering field.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] Residual stress is the main cause of coating cracking, and a large part of the residual stress comes from the thermal stress formed by the difference in thermal expansion coefficients between the coating material and the substrate material. Among them, the thermal expansion characteristics in the alloy are mainly determined by the positive thermal expansion caused by the anharmonic vibration of the alloy material's lattice and the superposition of the magnetic volume effect.
[0008] Based on this, this application uses Fe powder, Ni powder and Co powder with spontaneous magnetic volume effect as the basis, combines the design concept of multi-principal component high entropy alloy materials, mixes with Cr powder to prepare Fe-Co-Ni-Cr multi-principal component alloy powder, and then deposits it on the surface of the metal substrate through electromagnetic assisted laser deposition to form a deposition coating.
[0009] During the forming process of the deposited coating, an electromagnetic field is generated through a static magnetic field and a direct current, thereby generating a Lorentz force. In the process of forming a molten pool by the molten metal powder, the Lorentz force can act on the solidification process of the molten pool, improve the mass transfer and heat transfer inside the molten pool, and thus improve the mechanical properties of the coating. In addition, since the static magnetic field and the direct current directly generate electromagnetic effects, the Lorentz force can refine the microstructure of the coating and distribute it more evenly; at the same time, the refinement effect on the microstructure of the coating can be distributed deep in the coating, avoiding the occurrence of the skin effect. According to the Hall-Petch criterion, the strength of the material is positively correlated with the inverse of the grain size. Therefore, the refinement of the microstructure can improve the mechanical properties of the coating, and the efficiency has been greatly improved compared to the alternating magnetic field assisted laser metal deposition.
[0010] In this application, the deposition coating formed by electromagnetic-assisted laser deposition using high-purity Fe powder, Ni powder, Co powder and Cr powder as multi-principal alloy powder has the characteristic of low thermal expansion coefficient, with an average thermal expansion of 1.8×10 -6 / K, coating hardness is 750-860HV.
[0011] Specifically, the raw materials for preparing the deposited coating include, by mass percentage, 41.7-44.0% Fe powder, 9.4-13.7% Ni powder, 7.6-8.0% Cr powder, and the rest Co powder, wherein the purity of Fe powder, Ni powder, Co powder, and Cr powder is ≥ 98%. Preferably, the raw materials for preparing the deposited coating include, by mass percentage, 41.8% Fe powder, 9.4% Ni powder, 7.6% Cr powder, and 41.2% Co powder.
[0012] The present application provides a method for preparing a multi-principal alloy deposition coating with a low expansion coefficient, the method comprising:
[0013] S01: Fe powder, Ni powder, Cr powder and Co powder were weighed respectively according to the mass ratio, put into a ball mill and dry-milled for 1-3 hours to obtain a mixed powder with a mesh size of 200-400 mesh.
[0014] After accurately weighing high-purity Fe powder, Ni powder, Cr powder and Co powder according to the proportion, pour them into a ball mill and dry grind them for 1-3 hours to control the mesh size of the mixed powder between 200-400 meshes to obtain a mixed powder with a mesh size of 200-400 meshes. Among them, the mass percentages of high-purity Fe powder, Ni powder, Cr powder and Co powder are as follows: Fe powder 41.7-44.0%, Ni powder 9.4-13.7%, Cr powder 7.6-8.0%, and the rest is Co powder.
[0015] S02: spreading the mixed powder on the treated surface of the metal substrate and then drying it.
[0016] The metal substrate is polished with 150# SiC sandpaper to remove impurities on the surface. The polished surface of the metal substrate is required to be flat, and finally cleaned with anhydrous ethanol in an ultrasonic cleaning machine. The metal substrate in this application is various types of carbon steel and stainless steel.
[0017] The mixed powder is mixed with anhydrous ethanol and then spread on the treated metal substrate surface, wherein the thickness of the mixed powder is 1.1-1.5 mm. The metal substrate spread with the mixed powder is placed in a vacuum drying furnace and dried at a temperature of 200-300°C for 0.5-1h to remove moisture on the metal substrate surface and anhydrous ethanol in the mixed powder.
[0018] S03: Perform electromagnetic-assisted laser metal deposition on the dried metal substrate to obtain a deposited coating.
[0019] Place the dried metal substrate on the Figure 1 Electromagnetic-assisted laser metal deposition is performed on the electromagnetic-assisted laser metal deposition workbench shown to obtain a deposited coating. The processing parameters of electromagnetic-assisted laser metal deposition are: laser power: 800-1500W; scanning speed: 3-8mm / s; spot diameter: 3-6mm; DC current: 2-10A; magnetic field strength: 0.1-0.5T; high-purity nitrogen is used as the protective gas, and the flow rate is set at 30-40L / min.
[0020] The present invention has the following beneficial effects:
[0021] (1) This application uses Fe powder, Ni powder and Co powder with spontaneous magnetic volume effect as the basis, combined with the design concept of multi-principal high entropy alloy materials, and mixes with Cr powder to prepare Fe-Co-Ni-Cr multi-principal alloy powder, and then deposits it on the surface of the metal substrate by electromagnetic assisted laser deposition to form a deposition coating. The deposition coating has the characteristics of low thermal expansion coefficient, with an average thermal expansion coefficient of 1.8×10 -6 / K, the coating hardness is 750-860HV; the internal microstructure of the deposited coating is dense, without defects such as cracks and pores.
[0022] (2) During the deposition coating forming process in the present application, the static magnetic field and the direct current generate an electromagnetic field, which in turn generates the Lorentz force. During the process of the molten metal powder forming a molten pool, the Lorentz force can act on the solidification process of the molten pool, improve the mass transfer and heat transfer inside the molten pool, and thus improve the mechanical properties of the coating. In addition, the Lorentz force can also refine the microstructure of the coating and distribute it more evenly; at the same time, the refinement effect on the microstructure of the coating can be distributed deep in the coating, avoiding the occurrence of the skin effect. According to the Hall-Petch criterion, the strength of the material is positively correlated with the inverse of the grain size. Therefore, the refinement of the microstructure can improve the mechanical properties of the coating, and has greatly improved the efficiency compared to the alternating magnetic field assisted laser metal deposition.
[0023] (3) The electromagnetic assisted forming method in this application will not change the type of phase of the deposited coating and has little effect on the average thermal expansion coefficient, but it will affect the microstructure of the deposited coating. Therefore, by changing the current of the electromagnetic field and the size of the static magnetic field, the microstructure of the deposited coating can be easily and quickly improved, and the relevant mechanical properties of the coating can be adjusted to meet the needs of various working conditions.
[0024] (4) The deposited coating in this application has the characteristics of a high entropy alloy, excellent mechanical properties, and low material price, and is suitable for mass production.
[0025] (5) The electromagnetically assisted laser metal deposition equipment in this application has the characteristics of miniaturization and easy disassembly, and can operate in a limited working space. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The electromagnetic-assisted laser metal deposition device used in the embodiment of the present application;
[0027] Figure 2 This is the XRD (X-Ray Diffractometer) diagram of the multi-principal alloy deposition coating prepared in Example 1 of the present application;
[0028] Figure 3 This is the XRD diagram of the multi-principal alloy deposition coating prepared in Comparative Example 1 of the present application;
[0029] Figure 4 This is a SEM (scanning electron microscope) image of the multi-principal alloy deposition coating prepared in Example 1 of the present application;
[0030] Figure 5 This is a SEM image of the multi-principal alloy deposition coating prepared in Comparative Example 1 of the present application;
[0031] Figure 6This is a thermal expansion curve diagram of the multi-principal alloy deposition coating prepared in Example 1 of the present application;
[0032] Figure 7 This is a thermal expansion curve diagram of the multi-principal alloy deposition coating prepared in Comparative Example 1 of the present application;
[0033] Figure 8 This is a thermal expansion curve diagram of the multi-principal alloy deposition coating prepared in Comparative Example 2 of the present application;
[0034] Fig. 9 This is a thermal expansion curve diagram of the multi-principal alloy deposition coating prepared in Comparative Example 3 of the present application;
[0035] Symbols represent:
[0036] 1-positive DC electrode plate, 2-negative DC electrode plate, 3-substrate, 4-NdFeB permanent magnet, 5-pre-set powder. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further explained and illustrated by means of specific embodiments below.
[0038] Example 1
[0039] An embodiment of the present application provides a multi-principal alloy deposition coating with a low expansion coefficient. The raw materials for preparing the deposition coating include, by mass percentage, 41.8% Fe powder, 9.4% Ni powder, 7.6% Cr powder and 41.2% Co powder.
[0040] The method for preparing the deposited coating comprises:
[0041] S101: After accurately weighing high-purity Fe powder, Ni powder, Cr powder and Co powder according to the ratio, pour them into a ball mill and dry grind them for 3 hours to obtain a mixed powder with a mesh size of 300 mesh.
[0042] S102: Use 150# SiC sandpaper to polish the carbon steel surface to remove surface impurities. Mix the mixed powder with anhydrous ethanol and spread it on the treated carbon steel surface, where the thickness of the mixed powder is 1.3mm. Put the carbon steel covered with the mixed powder into a vacuum drying furnace and dry it at 250℃ for 1h to remove moisture on the carbon steel surface and anhydrous ethanol in the mixed powder.
[0043] S103: Place the dried carbon steel in the Figure 1On the electromagnetic-assisted laser metal deposition workbench shown, electromagnetic-assisted laser metal deposition is performed under the action of the positive DC electrode plate 1, the negative DC electrode plate 2 and the NdFeB permanent magnet 4 to obtain a deposited coating. The processing parameters of the electromagnetic-assisted laser metal deposition are: laser power: 1000W; scanning speed: 5mm / s; spot diameter: 5mm; DC current: 8A; magnetic field strength: 0.3T; high-purity nitrogen is used as the protective gas, and the flow rate is set at 35L / min.
[0044] Example 2
[0045] An embodiment of the present application provides a multi-principal alloy deposition coating with a low expansion coefficient. The raw materials for preparing the deposition coating include, by mass percentage, 42.0% Fe powder, 10.0% Ni powder, 7.8% Cr powder and 40.2% Co powder.
[0046] The method for preparing the deposited coating comprises:
[0047] S201: After accurately weighing high-purity Fe powder, Ni powder, Cr powder and Co powder according to the ratio, pour them into a ball mill and dry grind them for 1 hour to obtain a mixed powder with a mesh size of 200 mesh.
[0048] S202: Use 150# SiC sandpaper to polish the carbon steel surface to remove surface impurities. Mix the mixed powder with anhydrous ethanol and spread it on the treated carbon steel surface, where the thickness of the mixed powder is 1.1mm. Put the carbon steel covered with the mixed powder into a vacuum drying furnace and dry it at 200℃ for 0.5h to remove moisture on the carbon steel surface and anhydrous ethanol in the mixed powder.
[0049] S203: Place the dried carbon steel in the Figure 1 On the electromagnetic-assisted laser metal deposition workbench shown, electromagnetic-assisted laser metal deposition is performed under the action of the positive DC electrode plate 1, the negative DC electrode plate 2 and the NdFeB permanent magnet 4 to obtain a deposited coating. The processing parameters of the electromagnetic-assisted laser metal deposition are: laser power: 800W; scanning speed: 3mm / s; spot diameter: 3mm; DC current: 3A; magnetic field strength: 0.1T; high-purity nitrogen is used as the protective gas, and the flow rate is set at 30L / min.
[0050] Example 3
[0051] An embodiment of the present application provides a multi-principal alloy deposition coating with a low expansion coefficient. The raw materials for preparing the deposition coating include, by mass percentage, 43.0% Fe powder, 11.0% Ni powder, 7.9% Cr powder and 38.1% Co powder.
[0052] The method for preparing the deposited coating comprises:
[0053] S301: After accurately weighing high-purity Fe powder, Ni powder, Cr powder and Co powder according to the ratio, pour them into a ball mill and dry grind them for 1.5 hours to obtain a mixed powder with a mesh size of 220 mesh.
[0054] S302: Use 150# SiC sandpaper to polish the carbon steel surface to remove surface impurities. Mix the mixed powder with anhydrous ethanol and spread it on the treated carbon steel surface, where the thickness of the mixed powder is 1.2mm. Put the carbon steel covered with the mixed powder into a vacuum drying furnace and dry it at 240℃ for 0.5h to remove moisture on the carbon steel surface and anhydrous ethanol in the mixed powder.
[0055] S303: Place the dried carbon steel in the Figure 1 On the electromagnetic-assisted laser metal deposition workbench shown, electromagnetic-assisted laser metal deposition is performed under the action of the positive DC electrode plate 1, the negative DC electrode plate 2 and the NdFeB permanent magnet 4 to obtain a deposited coating. The processing parameters of the electromagnetic-assisted laser metal deposition are: laser power: 900W; scanning speed: 4mm / s; spot diameter: 4mm; DC current: 2A; magnetic field strength: 0.2T; high-purity nitrogen is used as the protective gas, and the flow rate is set at 32L / min.
[0056] Example 4
[0057] An embodiment of the present application provides a multi-principal alloy deposition coating with a low expansion coefficient. The raw materials for preparing the deposition coating include, by mass percentage, 41.7% Fe powder, 13.7% Ni powder, 8.0% Cr powder and 36.6% Co powder.
[0058] The method for preparing the deposited coating comprises:
[0059] S401: After accurately weighing high-purity Fe powder, Ni powder, Cr powder and Co powder according to the ratio, pour them into a ball mill and dry grind them for 2 hours to obtain a mixed powder with a mesh size of 280 mesh.
[0060] S402: Use 150# SiC sandpaper to polish the carbon steel surface to remove surface impurities. Mix the mixed powder with anhydrous ethanol and spread it on the treated carbon steel surface, where the thickness of the mixed powder is 1.4mm. Put the carbon steel covered with the mixed powder into a vacuum drying furnace and dry it at 280℃ for 1h to remove moisture on the carbon steel surface and anhydrous ethanol in the mixed powder.
[0061] S403: Place the dried carbon steel in the Figure 1On the electromagnetic-assisted laser metal deposition workbench shown, electromagnetic-assisted laser metal deposition is performed under the action of the positive DC electrode plate 1, the negative DC electrode plate 2 and the NdFeB permanent magnet 4 to obtain a deposited coating. The processing parameters of the electromagnetic-assisted laser metal deposition are: laser power: 1200W; scanning speed: 6mm / s; spot diameter: 4mm; DC current: 8A; magnetic field strength: 0.5T; high-purity nitrogen is used as the protective gas, and the flow rate is set at 36L / min.
[0062] Example 5
[0063] An embodiment of the present application provides a multi-principal alloy deposition coating with a low expansion coefficient. The raw materials for preparing the deposition coating include, by mass percentage, 44.0% Fe powder, 12.1% Ni powder, 7.8% Cr powder and 36.1% Co powder.
[0064] The method for preparing the deposited coating comprises:
[0065] S501: After accurately weighing high-purity Fe powder, Ni powder, Cr powder and Co powder according to the ratio, pour them into a ball mill and dry grind them for 2.5 hours to obtain a mixed powder with a mesh size of 380 mesh.
[0066] S502: Use 150# SiC sandpaper to polish the carbon steel surface to remove surface impurities. Mix the mixed powder with anhydrous ethanol and spread it on the treated carbon steel surface, where the thickness of the mixed powder is 1.4mm. Put the carbon steel covered with the mixed powder into a vacuum drying furnace and dry it at 260℃ for 1h to remove moisture on the carbon steel surface and anhydrous ethanol in the mixed powder.
[0067] S503: Place the dried carbon steel in the Figure 1 On the electromagnetic-assisted laser metal deposition workbench shown, electromagnetic-assisted laser metal deposition is performed under the action of the positive DC electrode plate 1, the negative DC electrode plate 2 and the NdFeB permanent magnet 4 to obtain a deposited coating. The processing parameters of the electromagnetic-assisted laser metal deposition are: laser power: 1500W; scanning speed: 8mm / s; spot diameter: 6mm; DC current: 10A; magnetic field strength: 0.5T; high-purity nitrogen is used as the protective gas, and the flow rate is set at 40L / min.
[0068] Comparative Example 1
[0069] In Comparative Example 1 provided in the present application, the raw materials and preparation method of the deposited coating are the same as those in Example 1, and only the processing parameters of the electromagnetic-assisted laser metal deposition are different. The processing parameters of the electromagnetic-assisted laser metal deposition in Comparative Example 1 are: laser power: 1000W; scanning speed: 5mm / s; spot diameter: 5mm; high-purity nitrogen is used as the protective gas, and the flow rate is set at 35L / min.
[0070] Comparative Example 2
[0071] In Comparative Example 2 provided in the present application, the raw materials for preparing the deposited coating include, by mass percentage, 41.8% Fe powder, 9.4% Ni powder, 7.6% Cr powder, 6% Al powder and 35.2% Co powder. The preparation method of the deposited coating is the same as that of Example 1.
[0072] Comparative Example 3
[0073] In Comparative Example 3 provided in the present application, the raw materials for preparing the deposited coating include, by mass percentage, 31% Fe powder, 15% Ni powder, 12% Cr powder and 42% Co powder. The preparation method of the deposited coating is the same as that of Example 1.
[0074] The deposited coatings obtained by deposition in Example 1 and Comparative Example 1 were subjected to XRD, SEM and thermal expansion tests, respectively. Figure 2-7 At the same time, the deposited coatings obtained in Comparative Examples 2 and 3 were subjected to thermal expansion tests, and the thermal expansion of the deposited coatings was respectively obtained. Figure 8 , 9 .
[0075] Compare with Figure 2 , 3 It can be seen that the phase of the deposited coating formed by deposition in Example 1 is mainly composed of a BCC phase structure, and the phase of the deposited coating formed by deposition in Comparative Example 1 is mainly composed of a BCC phase structure. This shows that under the same raw material ratio, the electromagnetic effect does not change the phase type of the deposited coating.
[0076] Compare with Figure 4 , 5 It can be seen that the microscopic surfaces of the deposited coatings formed by the deposition of Example 1 and Comparative Example 1 have no defects such as cracks and holes, and the microscopic surfaces of the deposited coatings are mainly composed of dendrites, wherein the average dendrite size of the deposited coating in Example 1 is 8.1 mm, and the average dendrite size of the deposited coating in Comparative Example 1 is 11.2 mm, which is slightly larger than the dendrite size of the deposited coating in Example 1. This shows that under the same raw material ratio, electromagnetic action can significantly refine the microstructure of the deposited coating, and the dendrite size is smaller and more evenly distributed.
[0077] Compare with Figure 6 , 7It can be seen that the average thermal expansion coefficient of the deposited coating formed by the deposition in Example 1 is 1.78×10 -6 / K, the average thermal expansion coefficient of the deposited coating formed by the deposition of comparative example 1 is 1.85×10 -6 / K, which is slightly larger than the average thermal expansion coefficient of the deposited coating formed by deposition in Example 1. This shows that under the same raw material ratio, the electromagnetic effect has a small effect on the average thermal expansion coefficient of the deposited coating.
[0078] Compare with Figure 6 , 8 It can be seen that the average thermal expansion coefficient of the deposited coating formed by the deposition in Example 1 is 1.78×10 -6 / K, the average thermal expansion coefficient of the deposited coating formed by the deposition in Comparative Example 2 is 13.7×10 -6 / K, which is much higher than the average thermal expansion coefficient of the deposited coating formed by deposition in Example 1. This shows that the deposited coating provided in the embodiment of the present application has a lower average thermal expansion coefficient only when it is composed of high-purity Fe powder, Ni powder, Cr powder and Co powder, that is, the components in the composition of the deposited coating in the present application are not selected arbitrarily.
[0079] Compare with Figure 6 , 9 It can be seen that the average thermal expansion coefficient of the deposited coating formed by the deposition in Example 1 is 1.78×10 -6 / K, the average thermal expansion coefficient of the deposited coating formed by the deposition of comparative example 3 is 9.7×10 -6 / K, which is much higher than the average thermal expansion coefficient of the deposited coating formed by deposition in Example 1. This shows that under the condition of the same raw material composition, changing the ratio content can significantly affect the average thermal expansion coefficient of the deposited coating. Therefore, only within the ratio range provided in this application, the deposited coating has a lower average thermal expansion coefficient.
[0080] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A multi-principal alloy deposition coating with a low expansion coefficient, characterized in that: The deposited coating is based on Fe powder, Ni powder and Co powder with spontaneous magnetovolume effect, which are mixed with Cr powder and then deposited on the carbon steel surface by laser through the electromagnetic field assisted laser deposition generated by static magnetic field and direct current to form a low expansion coefficient of 1.8×10 -6 / K, deposited coating whose main phase is BCC phase; The hardness of the deposited coating is 750-860HV; wherein, the raw materials for preparing the deposited coating include, by mass percentage, 41.7-44.0% Fe powder, 9.4-13.7% Ni powder, 7.6-8.0% Cr powder, and the rest is Co powder.
2. The multi-principal alloy deposition coating with low expansion coefficient according to claim 1, characterized in that: The raw materials for preparing the deposited coating include, by mass percentage, 41.8% Fe powder, 9.4% Ni powder, 7.6% Cr powder, and 41.2% Co powder.
3. The multi-principal alloy deposition coating with low expansion coefficient according to claim 1, characterized in that: The purity of Fe powder, Ni powder, Cr powder and Co powder is ≥98%.
4. A method for preparing a multi-principal alloy deposition coating with a low expansion coefficient as claimed in claim 1, characterized in that: include: Weigh Fe powder, Ni powder, Cr powder and Co powder according to the mass ratio, put them into a ball mill and dry grind them for 1-3 hours to obtain a mixed powder with a mesh size of 200-400 mesh; The mixed powder is spread on the treated surface of the metal substrate and then dried; The dried metal substrate is subjected to electromagnetic-assisted laser metal deposition to obtain a deposited coating.
5. The method for preparing a multi-principal alloy deposition coating with a low expansion coefficient according to claim 4, characterized in that: The processing parameters of the electromagnetic-assisted laser metal deposition are: laser power: 800-1500W; scanning speed: 3-8mm / s; spot diameter: 3-6mm; DC current: 2-10A; magnetic field strength: 0.1-0.5T; high-purity nitrogen is used as the protective gas, and the flow rate is set at 30-40L / min.
6. The method for preparing a multi-principal alloy deposition coating with a low expansion coefficient according to claim 4, characterized in that: The drying temperature is 200-300°C and the drying time is 0.5-1h.
7. The method for preparing a multi-principal alloy deposition coating with a low expansion coefficient according to claim 4, characterized in that: The paving thickness of the mixed powder on the surface of the metal substrate is 1.1-1.5 mm.
Citation Information
Patent Citations
Preparation method of ultrasonic / magnetic field composite auxiliary laser cladding high-temperature-oxidation-resistant homogeneous high-entropy alloy protective coating
CN116445909A